Movement patterns of common cranes at European stopover sites - Larsson, Elin (2016)
The common crane Grus grus is a migratory bird with a wide distribution across Europe and Asia. During the migration the cranes rest at stopover sites were they roost in wetlands and forage on surrounding fields in the farmland. Due to an increase of the European population over the last decades, damage to crops has increased and so the conflicts between cranes and farmers. Therefore, knowledge about the movement of cranes is not only important for an increased understanding of the ecology and behaviour of the species, but also important from a crop damage preventative management perspective. This study has investigated the size of activity areas and flight distances from the roost of juvenile cranes on different stopover sites during the autumn migration, by using GPS transmitters. The results showed that average size of activity area was 31.5 km2 and the average flight distance from the roost was 4.5 km. I found significant variation in both size of activity area and flight distance from roost between the countries along the flyway. Activity areas also varied between stopover sites and no clear latitudinal trend was found, which indicates that the variation rather depend on differences in local conditions. My study provides insight into the movement pattern of cranes, which could be applied when planning crop preventative measures in agricultural areas.